Strategi Peningkatan Pengamalan Keagamaan Siswa Melalui Penerapan Pendekatan Deep Learning di Madrasah Ibtidaiyah Al-Barokah - Marfu’ah Ukhtiani; Sigit Dwi Laksana; Anip Dwi Saputro (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This research demonstrates that the implementation of the deep learning strategy, through optimizing learning tools, engaging in crisis Q&A sessions, and linking the material to everyday life, successfully improved the quality of students' religious practice. This approach, which focuses on deepening fundamental meanings, has been proven to have a significant impact on improving discipline in daily worship, such as the Dhuha prayer, murojaah prayer, and congregational Dhuhur prayer. It also fosters the development of honest character based on faith awareness, as well as the growth of genuine social concern. The success of this program is supported by the consistent commitment of teachers to monitoring students' emotional and character development daily. While obstacles such as the residual learning culture that focuses solely on grades and differences in family parenting styles were successfully overcome through ongoing communication with parents. Overall, this research concludes that deep learning has the potential to transform elementary school-aged children's religious thinking patterns from mere formality to a deeply rooted moral and spiritual commitment.